Love and money : queers, class, and cultural production - Henderson, Lisa (Critical cultural communication., 2013)
"Love and Money argues that we can't understand contemporary queer cultures without looking through the lens of social class. Resisting old divisions between culture and economy, identity and privilege, left and queer, recognition and redistribution, Love and Money offers supple approaches to capturing class experience and class form in and around queerness. Contrary to familiar dismissals, not every queer television or movie character is like Will Truman on Will and Grace--rich, white, healthy, professional, detached from politics, community, and sex. Through ethnographic encounters with readers and cultural producers and such texts as Boys Don't Cry, Brokeback Mountain, By Hook or By Crook, and wedding announcements in the New York Times, Love and Money sees both queerness and class across a range of idioms and practices in everyday life. How, it asks, do readers of Dorothy Allison's novels use her work to find a queer class voice? How do gender and race broker queer class fantasy? How do independent filmmakers cross back and forth between industry and queer sectors, changing both places as they go and challenging queer ideas about bad commerce and bad taste? With an eye to the nuances and harms of class difference in queerness and a wish to use culture to forge queer and class affinities, Love and Money returns class and its politics to the study of queer life."--Publisher's website.